Hedging of exchange rate risk and regression dependence - Udo Broll; Kit-Pong Wong (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
The paper presents a model of a risk-averse exporting firm under exchange rate risk. We focus on the economic implications of basis risk. It is shown that the regression dependence assumptions between spot and futures exchange rates are essential in analyzing optimal hedging and export decisions. When the spot exchange rate and the futures exchange rate are imperfectly correlated we show that the firm adopts an over hedge when the exchange rate risk exposure is convex and an under hedge when the risk exposure is concave given the unbiasedness of the currency futures market.
Keywords: F21; F31; 330; exchange rate risk; hedging; regression dependence; Währungsmanagement; Hedging; Außenhandelssektor; Devisenmarkt; Währungsderivat; Regression; Theorie